Piezoelectric system with software management - Fandiño Gómez, Jayr Antonio; Cortes López, Segundo Leonardo; Valderrama García, Leonardo (Ingeniería Solidaria, 2023)
This article is a product of the project "Piezoelectric system with software management", developed by Jayr Antonio Fandiño Gómez in conjunction with the University of Cundinamarca Ubaté sectional.Objective: To develop a source of clean energy with the help of piezoelectric materials, to take advantage of the passage of people within the University of Cundinamarca, Ubaté sectional, generating savings of "energy" resources.Method: Different phases have been carried out using different sensors in order to create a better product which is capable of generating clean energy that can be used for the lighting supply of this public space.Results: A piezoelectric tablet of large dimensions and optimized has been created, which was implemented for testing within the University of Cundinamarca, Ubaté sectional generating results that led to the creation of a NoSQL database.Conclusion: By implementing a new renewable energy system in an area where there are environmental concerns, awareness of the different problems generated by the advancement of technology will be generated.Limitation of the study: The acquisition of the sensors can be complicated due to the fact that this product is mostly created abroad.
Keywords: piezoelectric; pressure; electricity; clean energy; software